Nitrogen in Agriculture - Physiological, Agricultural and Ecological Aspects [Working Title] 2021
DOI: 10.5772/intechopen.95359
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Residue Management for Effective Use of Mineralized Nitrogen in Greenhouse Tomato Production

Abstract: Adequate residue management may enhance the benefits of cover crops on greenhouse tomato (Solanum lycopersicum L.) productivity, soil N pool, N cycling, and environmental quality. Regardless of management, cover crops may maintain or increase soil N storage at 10 cm depth compared with bare fallow. Cover crops may also enhance microbial biomass N, as a result, soil N availability may increase with cover crops, except rye (Secale cereale L.), more so with hairy vetch (Vicia villosa R.; HV) incorporation than HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…However, because of the relatively high levels of external inputs, the legume cover crops increased the surplus of N in the system, which may result in environmental losses, while rye was more effective as a cover crop, to minimize N surplus levels from the system [217]. Based on multi-year cover crop evaluations conducted in Japan, including 15 N studies, a combined 2:1 hairy vetch/rye planting ratio was also found to improve the mineralization and synchronization of N release by the individual species, with the N uptake demand of tomato, along with an increase in the overall soil N pool and N cycling [218].…”
Section: System Diversification To Improve Nuementioning
confidence: 99%
“…However, because of the relatively high levels of external inputs, the legume cover crops increased the surplus of N in the system, which may result in environmental losses, while rye was more effective as a cover crop, to minimize N surplus levels from the system [217]. Based on multi-year cover crop evaluations conducted in Japan, including 15 N studies, a combined 2:1 hairy vetch/rye planting ratio was also found to improve the mineralization and synchronization of N release by the individual species, with the N uptake demand of tomato, along with an increase in the overall soil N pool and N cycling [218].…”
Section: System Diversification To Improve Nuementioning
confidence: 99%